2012
DOI: 10.1371/journal.pone.0042047
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Exploration of Viruses throughout the Indian Ocean

Abstract: The characterization of global marine microbial taxonomic and functional diversity is a primary goal of the Global Ocean Sampling Expedition. As part of this study, 19 water samples were collected aboard the Sorcerer II sailing vessel from the southern Indian Ocean in an effort to more thoroughly understand the lifestyle strategies of the microbial inhabitants of this ultra-oligotrophic region. No investigations of whole virioplankton assemblages have been conducted on waters collected from the Indian Ocean or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
110
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 82 publications
17
110
2
Order By: Relevance
“…These seven viromes, all from the ocean surface, included four from the Indian Ocean (13) and three from the Pacific Ocean (Table 1 and Table S3; see SI Materials and Methods for the selection process, brief description, and sequence processing). Each read from the selected viromes was used as a query in BLASTN analyses against a genome database that included HMO-2011 and 4,541 other viruses and was assigned to a single best-matching reference genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These seven viromes, all from the ocean surface, included four from the Indian Ocean (13) and three from the Pacific Ocean (Table 1 and Table S3; see SI Materials and Methods for the selection process, brief description, and sequence processing). Each read from the selected viromes was used as a query in BLASTN analyses against a genome database that included HMO-2011 and 4,541 other viruses and was assigned to a single best-matching reference genome.…”
Section: Resultsmentioning
confidence: 99%
“…Recent metagenomic studies of the oceans have revealed the numerous novel genetic repertoires of marine viromes (8)(9)(10)(11)(12)(13)(14). However, most genome fragments in these viromes cannot be categorized into any known viral group (8,9,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a direct comparison of protein-coding gene content between fractions was not presented, and high-resolution taxonomic surveys from these analyses are not available. Although such comparisons identified functional differences in size-fractionated picoeukaryote ) and viral (Williamson et al, 2012) communities, to the best of our knowledge only two other studies Smith et al 2013), focusing on temperate sites in the North Pacific, have directly compared microbial (Bacteria and Archaea) functional gene content between filter size fractions. Here, we use metagenome and 16S rRNA gene amplicon sequencing to compare microbial communities from two size classes in the ETSP OMZ.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, we have generated a g23 tree that combines several viral metagenomics data sets from freshwater environments (Lake Pavin, France [102] and El Berbera Saharan pond [107]) and ma-rine environments (M6O1K, Indian Ocean [108] and LJ12S and LJ26S, Pacific Ocean [109]) with isolated T4-like phages (Fig. 1).…”
Section: Signature Genes Used In Metagenomic Data Setsmentioning
confidence: 99%